Tecnologias da informação e comunicação na socialização do conhecimento: um estudo de caso na Biblioteca Central da Universidade Federal da Paraíba - Cunha, Viviane Lima da (2014)
This study searched to investigate how the Central Library of UFPB from the implementation of TCI s and the technological tools provided by Instituto Brasileiro de Informação Ciência e Tecnologia - Comut, CCN and BDTD - in managing services, contributes to the process of socialization of scientific knowledge at university. In the methodological aspect, the research is characterized as a case study qualitative and descriptive character. Data were obtained through bibliographic and documentary sources, as well as through semi-structured interviews, which allowed us to know the vision of the seven managers - working in the Technical Processes Division; the Division of Services for Users and Managers of Central Library - about the topic searched. To systematize and analyze the data, was adopted the method of content analysis. Based on these results, we conclude that the Central Library /UFPB directs scrips towards socialization of knowledge, access to scientific communication and the use of TIC s in the management of their activities, however, the institution still does not work effectively in this dimension, because only the use of TCI s is not enough to achieve this goal. The use of informacion and comumunication technologies requires the Central Library directing their scrips not only to aspects related to the management of the collection. Involves mainly the development of policies of fortification of its role as provider of information access, operating on socialization of knowledge and therefore fulfilling its mission of providing informational support to teaching, research and extension programs of UFPB.